▼Pylorid, H. pylori and peptic ulcer. Issue 9 (September 1996) - Unknown
Abstract : In most people with a duodenal or gastric ulcer, the stomach mucosa is infected with Helicobacter pylori.1 If this infection is eradicated the risk of ulcer relapse is greatly reduced. Ranitidine bismuth citrate (Pylorid - GlaxoWellcome) was licensed last year and promoted as a drug "designed to be used in combination with clarithromycin for effective eradication of H. pylori". How valuable is it in the management of peptic ulcer disease?